Potential Targets for the Protective Effect of Astaxanthin on Ethanol-induced Damage in Rat Liver Mitochondria - Krestinina, Olga; Krestinin, Roman; Odinokova, Irina; Sotnikova, Linda; Baburina, Yulia (Current Medicinal Chemistry, 2025)
BackgroundAlcohol intoxication leads to multiple degenerative disorders in the structure and function of mitochondria. The mechanisms underlying these disorders, as well as ways to prevent them, are an urgent task in biomedicine. We investigate the mechanism of the positive effect of AX on rat liver mitochondria after chronic alcohol administration and suggest the targets of its effects. In this work, we continued our studies of astaxanthin (AX) as a possible protector of mitochondria from the toxic effects of ethanol.MethodsIn our experiments, we used the Lieber-DeCarly model of chronic alcohol intoxication, which allows high-dose alcohol intake. Four groups of animals were used in the experiments: group 1 (control), group 2 (treated with AX), group 3 (treated with ethanol), and group 4 (treated with ethanol and AX together). Rat liver mitochondria (RLM) were isolated by the standard method modified in our laboratory. A multifunctional chamber with built-in electrodes was used to determine mitochondrial functions. Electrophoresis followed by Western blot analysis was used to detect mitochondrial proteins. Statistical significance was calculated using t-test Student-Newman- Keuls test.ResultsAX has been shown to have a positive effect on the functioning of the mitochondrial permeability transition pore (mPTP), the regulation of signaling pathways, as well as mitochondrial dynamics. It was found that AX is able to suppress the degenerative effect of alcohol on liver mitochondria. Targets for the protective action of AX in rat liver mitochondria (RLM) have been proposed.ConclusionThe discovered protective effect of AX on liver mitochondria during alcohol damage may contribute to the development of new strategies for the treatment of alcohol-induced damage.
Keywords: mitochondrial dysfunction